REVITALISASI PERAN KONSELOR DALAM PELAYANAN KONSELING PRA-NIKAH DI KUA - Lubis, Muhammad Alridho; Ayuningtias, Eka Wahyuni; Oktaviana, Vivi; Asrofi, Fauzan (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
The Office of Religious Affairs has services in the form of marriage formation and maintenance institutions. Counselors provide assistance and services to prospective brides and grooms in order to guide and provide insight regarding marriage as a provision for the prospective bride and groom so that the prospective bride and groom are able to establish themselves to live a married life. With premarital counseling, it is hoped that the prospective bride and groom will be able to build their household into a sakinah, mawadah, warahmah family. The purpose of this article is to analyze the urgency of the counselor's role in providing premarital counseling at KUA. The method used is a literature study by examining various sources related to pre-marital counseling, the role of counselors, and KUA services. From the literature review, the author obtained results that refer to the initial concept of premarital counseling services, the objectives of premarital counseling, the role of counselors in KUA. The conclusion of this article is that the role of counselors is very necessary to improve the quality of pre-marital counseling services at KUA. This is important to prepare the prospective bride and groom to face the challenges of married life. The author also recommends increasing collaboration between the KUA and educational institutions and community organizations in socializing the importance of pre-marital counseling.